IX Conference on the Utilization of Ultrasonic Methods for Studying the Properties of Condensed Matter, Žilina (Czechoslovakia), 23-25 August, 1984 - SOCZKIEWICZ, Eugeniusz (Archives of Acoustics, 1985)
The Ninth Conference on the Utilization of Ultrasonic Methods for Studying the Properties of Condensed Matter was held on 23-25 August, 1984 in Žilina (Czechoslovakia). The Conference was sponsored by the Physics Section of the Slovak Mathematicians and Physicists Association, the Acoustic Committee (Ultrasonics Subcommision) of the Czechoslovak Academy of Sciences, and organized by the Physics Department of the Technical University of Advanced Transport and Communication Engineering in Žilina, and the Physics Institute of the Slovak Academy of Sciences in Bratislava. RNDr. S. KOLNIK, CSc. was the chairman of the Organizing Committee of the Conference.